Knowledge, Attitudes and Practices of Hand Hygiene amongst Healthcare personnel of Mayo Hospital, Lahore - Fatima tu Zahara, Abeera Ishaq Butt, Fatima Arshad, Iqra Kabir, Muhammad Zeeshan Sarwar, Khadija Waheed, Syed Asghar Naqi (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To verify the knowledge, Attitude and Practices of hand hygiene amongst healthcare personnel of Mayo Hospital, Lahore. Study Design: A Cross-sectional study was carried among healthcare staff. Study Duration: September 2018-January 2019. Results: Overall, 600 doctors and nurses were enrolled in our study, 300 in each group. The mean knowledge score of doctors was 16.1±2.25 while that of nurses was 13.0±2.82. 13.6% of the doctors found to possess good attitude regarding hand hygiene but 29.6% of them had good practices. On the contrary, only 0.3% of the nurses had good attitude with 22.3% of them had good hand hygiene practices. Conclusion: Hand hygiene is one of the most effectual and simplest mean to avoid hospital acquired infections. Education of undergraduates is the basis of its implementation, in addition to the availability of the facilities. Keywords: Knowledge, Attitude, Practices, Hand hygiene.